Activewear for Malaysian women focusing on modesty style / Elia Md Zain and Sharifah Alwiah Syed Sahil - Md Zain, Elia; Syed Sahil, Sharifah Alwiah (Universiti Teknologi MARA, 2018)
Modest activewear is one of the alternative outfits to fulfill the needs of modesty looks while doing an activity for the Muslim especially women. There is lack of choices for activewear designs in the market and excessive attention towards Malaysian women which are concerned about modest appearances during their workout. (Ilyashov, 2017). The intention of designing modest activewear was to provide more options of activewear clothing line or leisure outfit for their active lifestyles. The objectives of this study were: 1. To identify the important features to be considered in designing modesty activewear design: 2. To experiment the potential materials and suitable designs for modesty activewear: 3. To contribute a module for designers and manufacturers in getting the suitable designs in relation to style and materials for modesty activewear. In order to achieve the objectives, this research has been conducted by using mixed methods which are observation session at four (4) selected location to study the current trend, styles and materials according to several sports brands, interviews with two (2) local experts in the apparel manufacturing industries and academicians, the questionnaires were distributed to fifty one (51) respondents around Klang Valley in order to gain the information about their acceptance of modesty activewear which were selected based on their involvement in sports. Experimentations were conducted during the preliminary and post-test in order to fulfil activewear designs which focused towards modesty look. As a conclusion, all of the objectives had been achieved in producing the activewear focusing on modesty style for women with the right materials.